Hubungan Media Game Online Dalam Meningkatkan Minat Belajar Pada Anak-Anak - Naila Umniati; Fajira Mahmudah; Diah Sawitri; Adam Malik Siregar; Ali Ikhwan (CV. ITTC INDONESIA, 2023)
The childhood period is also called the golden age because it is at that time that children will begin to learn from discipline, grammar to knowledge. It is necessary for parents to know what kind of methods the child needs in learning. Recently, online games have begun to spread, most people think that online games can have a bad or negative influence but this is not entirely true. The games or applications contained in this game-based learning model are great for improving students' imagination ability to think. With the implementation of the educational game-based learning process, it is hoped that the creation of creative and innovative learning so that it continues to generate interest and enthusiasm in children to continue to be enthusiastic about learning because of more fun methods.